Increase of Healthy Food Quality among the Kazakhstan Population - Z. Yessimsiitova ,; N. Ablaikhanova ,; S. Sagyndykova ,; G. Tussupbekova ,; M. Kulbayeva ,; G. Atanbayeva ,; M. Aitzhan ,; Z. Bissenbayeva, (Journal of Pharmacy and Nutrition Sciences, 2018)
At present, one of the most important urgent issues is the study of healthy nutrition of the population of Kazakhstan. Proper nutrition ensures the growth and development of children, contributes to the prevention of diseases, increase the capacity for work and prolong the life of people, while creating conditions for adequate adaptation to the environment. Most of the population of Kazakhstan because of technological processing, the use of inadequate food raw materials, influence of other causes, does not receive the necessary amount of essential components of food, which lead to illnesses, premature aging and shortening of life. The situation aggravates by the low cultural level of the population in matters of rational nutrition and the lack of skills for healthy lifestyles. In this regard, the main task in the work was to study methods of improving the health and quality of life of the population of Kazakhstan, especially those living in zones of environmental problems and contacting with harmful factors.